Teaching with writing and teaching to write: an interwoven approach by way of interdisciplinary collaboration - Carlino, Paula (2023)
How should we organize the teaching of the disciplines so that students make epistemic use of the writing tasks they are usually assigned? Among the different ways of teaching academic writing in higher education, this article discusses the interwoven approach, which consists of both teaching the disciplines with writing and teaching to write in an integrated way. We highlight its features and distinguish it from other approaches. We then illustrate it through the collaborative experience developed between an engineering instructor and a writing instructor over 18 months. Our approach contributes to improving the disciplinary instructor’s teaching practice, so that he/she not only assigns and evaluates reading and writing tasks but also teaches how to carry them out; likewise, we try to ensure that writing is used as an epistemic means of crafting disciplinary knowledge, and not only to communicate what has been learned. This article invites to deepen the debate about the teaching of reading, writing, and the genres required in university disciplines by explaining the approach that the GICEOLEM has developed over two decades, and by analyzing the similarities and differences with approaches that are subtly unalike.